Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Materi Aku Pribadi yang Unik Model Problem Based Learning (PBL) Berbantuan Audio Visual untuk Kelas X SMAS Karya Sedar Biru-Biru 2024/2025 - Julista Br Tarigan; YL. Sukestiyarno; Martina Murliani (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research was conducted at SMAS Karya Sedar Biru-Biru in Class X with the subjects of this study were 10 students. Based on the analysis of data on the initial reflection which still showed that the learning outcomes of students were still lacking, the research was conducted by implementing the Problem Based Learning (PBL) learning model in learning Unique Personal Humans to improve student learning outcomes. 1) The formulation of the problem in this study is: How to improve the learning outcomes of Catholic Religious Education on the material "Unique Personal Humans" through the Problem Based Learning model for class X students of SMAS Karya Sedar Biru-Biru Academic Year 2024/2025 2) How much is the increase in student learning outcomes after implementing the Problem Based Learning model for class X students of SMAS Karya Sedar Biru-Biru Academic Year 2024/2025? The purpose of this study was to determine the Improvement in Learning Outcomes of Unique Personal Humans by implementing the Problem Based Learning model for class X students of SMAS Karya Sedar Biru-Biru. Data collection techniques were observation and testing. The data analysis technique used was qualitative descriptive technique. According to the results of the research that has been conducted, the following conclusions were obtained: Learning activities using the Problem Based Learning model can improve student learning outcomes on the Unique Human Personality material from cycle I by 71% to 90% in cycle II. The increase that occurred from cycle I to cycle II was 19%